Structural Steelwork : Analysis and Design. - Ray, S. S. (Wiley-Blackwell [Imprint], John Wiley & Sons, Incorporated., 1998)
Annotation This manual, a companion to the book Reinforced Concrete, also by Ray, covers the design of structural steelwork elements in a logical, step-by-step fashion. The text is backed up by numerous illustrations, design charts and tables, and refers throughout to the relevant codes of practice. A large number of worked examples cover almost all types of structural steelwork elements, including more advanced techniques.
Keywords: Building, Iron and steel.; Steel, Structural.; elektronické knihy; electronic books